Clinical accuracy of dermatologists and nondermatologists in the diagnosis of dermatological diseases - Aamir Habib (Journal of the Pakistan Medical Association, 2023)
Objective: To compare the clinical diagnostic accuracy of dermatologists and non-dermatologists in the diagnosis of dermatological diseases. Method: The descriptive, cross-sectional study was conducted at the Dermatopathology department of a tertiary healthcare hospital in the Punjab province of Pakistan from January 1 to December 31, 2019, and comprised biopsy specimens of patients with diseases of the skin and subcutaneous tissue. The clinical diagnoses of general surgeons, otolaryngologists, dental/maxillofacial surgeons, plastic surgeons and gynaecologists were noted and compared with those of dermatologists in the light of histopathological findings. Data was analysed using SPSS 16. Results: Of the 386 specimens submitted, 113(29.3%) were sent by dermatologists and 273(70.7%) by non-dermatologists. Clinical diagnostic accuracy of dermatologists 92(81.4%) compared to non-dermatologists 137(50.2%) (p<0.005). The dermatologists diagnosed significantly more cases belonging to inflammatory and miscellaneous cutaneous diseases category accurately than non-dermatologists (p<0.005). Similarly, the dermatologists diagnosed significantly more cases of neoplastic disorders accurately than the non-dermatologists (p= 0.018). There was no significant difference in the clinical diagnostic accuracy of dermatologists and non-dermatologists in cases of cystic lesions (p>0.05). In the neoplastic category, no significant difference was found in the clinical accuracy of dermatologists and plastic surgeons (p=0.347). Conclusions: The specialised skills of dermatologists could not be matched by any other group of physicians. Key Words: Diagnostic accuracy, Dermatologist, Surgical excision, Dermatological diseases, Histopathological diagnosis.